Expert System using Artificial Intelligence Techniques for Diabetes - S.Saranya, M.VijayAnand, T.RajeshKumar, L.Vanitha,K.Kalaiselvi ,P. Suresh (Drugs and Cell Therapies in Hematology, 2021)
Diabetes Mellitus is one of the major risk prone diseases in the world. More than diabetes alone, it’s the consequences caused because of Diabetes is completely unknown to many, for even to some who are diabetic. The symptoms caused for each disease are totally unaware and left unnoticed, this leading to a several diseases due to being severely diabetic. This expert system for diabetes is for the diabetic and for the pre-diabetic patients to perform a self-test based on their symptoms. This expert system is designed in such a way that the patients can analyze their diabetic consequence disease by responding to the set of questions asked based on the symptoms on what the patients is undergoing and cross verifies with the systems knowledge base and provides with an appropriate suggestion. The analysis is processed by inference engine and then the result (disease) is displayed along with the treatments, causes, and further investigations. This expert system for diabetes helps the patients to analyze their risk level and it will help them to determine the department of doctors to which they should pay a visit for further consultation. This particular system is totally based on the responses recorded from the patient as a survey and the results are analyzed by our base system, such that the data provided by the patient leads to suitable consultation.